Functional dye as a comonomer in a water‐soluble polymer. Issue 13 (28th March 2015) - Zhang, Wenwen; Vinueza, Nelson R.; Datta, Preeta; Michielsen, Stephen
ABSTRACT In many applications, a functional additive is blended into a polymer matrix to enhance its properties. However, when the polymer and functional additive are applied to a surface, the functional molecule may be easily lost. In favorable cases, it may be possible to incorporate the additive directly into the polymer as a comonomer. In this study, a functionalized polymer has been obtained through the combination of linking a photodynamic, antimicrobial dye, Rose Bengal, to vinyl benzyl chloride via etherification and then polymerizing this into a water‐soluble polymer using chain growth copolymerization. Characterization of the efficiency of synthesis, solubility of the final product, and singlet oxygen production rate has been performed. Dialysis was used to determine the extent of incorporation of the dye into the polymer. The chemical structure of the intermediate produced through etherification has been verified. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1594–1599